2009
DOI: 10.1016/j.watres.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aryl hydrocarbon receptor agonists in sediments of Wenyu River, Beijing, China

Abstract: PAHs H4IIE Sediment a b s t r a c tAryl hydrocarbon receptor agonistic (Ah-agonistic) effects of 23 sediments from Wenyu River in Beijing, China were evaluated using the H4IIE cell bioassay. Five samples were selected for chemical analysis of most concerned Ah-agonists, i.e. polychlorinated dibenzo-p-dioxins (PCDDs), dibenzofurans (PCDFs), biphenyls (PCBs), and polycyclic aromatic hydrocarbons (PAHs). All raw sediment extracts induced significant Ah-agonistic effects, and the bioassay-derived 2,3,7,8-tetrachlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…There were no great differences between the EROD values among the ten sediment samples, indicating that AhR agonists were distributed rather homogeneously in TGR from Wanzhou to the great dam. The determined EROD TCDD EQ (bio-TEQ) amounts in the present study are comparable with ERODinducing potentials of sediments reported by some other studies, including sediments collected from harbors along the Dutch coast ranging from 0.2 to 136 pg TCDD EQ g −1 dw (Stronkhorst et al 2002) and from Osaka Bay, Japan with 3.7 to 140 pg TCDD g −1 dw (Takigami et al 2005) tested with H4IIE-luc hepatoma cell line after 24 h of exposure, as well as sediments collected from Wenyu River, China with 15 to 64 pg TCDD g −1 tested with H4IIE hepatoma cell line after 72 h of exposure (Luo et al 2009) and from Yeongil Bay, Korea ranging from 2.8 to 320 pg TCDD g −1 dw tested with H4IIE-luc hepatoma cell line after 72 h of exposure (Koh et al 2006). On the other hand, the EROD bio-TEQ amounts reported in our study are higher than those reported in sediments from west coast of South Korea with non-detectable to 11 pg TCDD g −1 dw and north coast of Bohai Sea, China with nondetectable to 28 pg TCDD g −1 dw (Hong et al 2012) and sediments from Meiliang Bay, Lake Taihu before the ecological remediation project ranging from 17.8 to 38.5 pg TCDD g −1 dw (Qiao et al 2009) which were all tested with H4IIE rat hepatoma cells after 72 h of exposure.…”
Section: Erod Activity Of Samplesmentioning
confidence: 99%
“…There were no great differences between the EROD values among the ten sediment samples, indicating that AhR agonists were distributed rather homogeneously in TGR from Wanzhou to the great dam. The determined EROD TCDD EQ (bio-TEQ) amounts in the present study are comparable with ERODinducing potentials of sediments reported by some other studies, including sediments collected from harbors along the Dutch coast ranging from 0.2 to 136 pg TCDD EQ g −1 dw (Stronkhorst et al 2002) and from Osaka Bay, Japan with 3.7 to 140 pg TCDD g −1 dw (Takigami et al 2005) tested with H4IIE-luc hepatoma cell line after 24 h of exposure, as well as sediments collected from Wenyu River, China with 15 to 64 pg TCDD g −1 tested with H4IIE hepatoma cell line after 72 h of exposure (Luo et al 2009) and from Yeongil Bay, Korea ranging from 2.8 to 320 pg TCDD g −1 dw tested with H4IIE-luc hepatoma cell line after 72 h of exposure (Koh et al 2006). On the other hand, the EROD bio-TEQ amounts reported in our study are higher than those reported in sediments from west coast of South Korea with non-detectable to 11 pg TCDD g −1 dw and north coast of Bohai Sea, China with nondetectable to 28 pg TCDD g −1 dw (Hong et al 2012) and sediments from Meiliang Bay, Lake Taihu before the ecological remediation project ranging from 17.8 to 38.5 pg TCDD g −1 dw (Qiao et al 2009) which were all tested with H4IIE rat hepatoma cells after 72 h of exposure.…”
Section: Erod Activity Of Samplesmentioning
confidence: 99%